0
$\begingroup$

Show $\lim\limits_{t \to \infty} e^{-t}\sum_{n=0}^{\infty}a_n\frac{t^n}{n!}=0$ if the sequence $\{a_n\}$ converges to limit 0.

So, If I could show that $\lim\limits_{t \to \infty} \sum_{n=0}^{\infty}a_n\frac{t^n}{n!}$ is finite then I am done as $\lim\limits_{t \to \infty} e^{-t}=0$. Now, $e^t=\sum_{n=0}^{\infty}\frac{t^n}{n!}$ converges by ratio test. How to show $\lim\limits_{t \to \infty} \sum_{n=0}^{\infty}a_n\frac{t^n}{n!}$ is convergent?

$\endgroup$
  • $\begingroup$ Do you mean $t^n$? $\endgroup$ – asdq Feb 12 '18 at 12:40
  • $\begingroup$ I didn't get you. Could you be a bit more specific? Where do you suggest a correction? $\endgroup$ – Dom Feb 12 '18 at 12:46
  • $\begingroup$ You wrote $t_n$ but I don't know what $t_n$ is supposed to be. $\endgroup$ – asdq Feb 12 '18 at 12:48
  • $\begingroup$ Yes, I got it now. Thanks! I edited the question. $\endgroup$ – Dom Feb 12 '18 at 12:51
0
$\begingroup$

If $a_n\to 0$ then for every $\varepsilon > 0$ there is some $N=N(\varepsilon)$ ensuring $|a_n|\leq \varepsilon$ for any $n\geq N$.
Let $M=M(\varepsilon)$ the maximum of $|a_n|$ for $n\in[0,N]$. We have $$ \left|\sum_{n\geq 0}a_n\frac{t^n}{n!}\right| \leq M\sum_{n=0}^{N}\frac{t^n}{n!}+\varepsilon e^t $$ hence $$ \left|\lim_{t\to +\infty} e^{-t}\sum_{n\geq 0}a_n\frac{t^n}{n!}\right|\leq \varepsilon +M\lim_{t\to +\infty}\sum_{n=0}^{N}\frac{t^n e^{-t}}{n!}\leq \varepsilon $$ and since $\varepsilon$ is arbitrary, the wanted limit is zero.

| cite | improve this answer | |
$\endgroup$
0
$\begingroup$

The power series certainly converges for every $t$, because if $A=\max\{|a_n|:n\in\mathbb{N}\}$, then $$ \left|\frac{a_nt^n}{n!}\right|\le A\frac{t^n}{n!} $$

Unfortunately for you, the series converges to a function $f(t)$ that can have infinite limit at $\infty$. For instance, if $a_n=1/(n+1)$, the series becomes $$ \sum_{n=0}^\infty\frac{t^n}{(n+1)!}=\frac{1}{t}\sum_{n=0}^\infty\frac{t^{n+1}}{(n+1)!}=\frac{1}{t}(e^t-1) $$ (for $t\ne0$) and $\lim_{t\to\infty}(e^t-1)/t=\infty$.

On the other hand, $$ \lim_{t\to\infty}\frac{(e^t-1)/t}{e^t}=0 $$ so the statement you want to prove holds for this case nonetheless.


For completeness, here'a an argument (similar to Jack's, of course).

Let's use the fact that $\lim_{n\to\infty}a_n=0$. Then, for every $\varepsilon>0$, there exists $N$ with $|a_n|<\varepsilon$. Thus we have (working for $t>0$) $$ |f(t)|\le\sum_{n=0}^N\frac{|a_n|}{n!}t^n+\varepsilon\sum_{n>N}\frac{t^n}{n!}= \sum_{n=0}^N\frac{|a_n|}{n!}t^n-\varepsilon\sum_{n=0}^N\frac{t^n}{n!} +\varepsilon\sum_{n\ge0}\frac{t^n}{n!}=p(t)+\varepsilon e^t $$ where $p(t)$ is a polynomial of degree at most $N$.

Since $\lim_{t\to\infty}\dfrac{p(t)}{e^t}=0$, you should be able to conclude.

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.